Maternité Et Risques Perçus Face Aux Examens Sanguins Et Au Test Du VIH-SIDA : Etude De Cas Dans Une Formation Sanitaire Urbaine De Bouaké (Côte D’ivoire) - Hilaire, Mazou Gnazegbo (European Scientific Journal, ESJ, 2017)
Pregnancy is a physiological condition that requires prenatal followup during which medical care ensures that complications in childbirth are prevented and that a healthy child is born as much as possible. It is therefore important for pregnant women to undergo a number of clinical examinations, including blood tests and HIV / AIDS testing, which are in the process of being integrated into the monitoring of women at the primary health care. However, pregnant women do not systematically use these practices in Urban Sanitary Training in Côte d’Ivoire generally and in Bouaké in particular. The free choice of women to submit to the various tests, the health benefits of which are the subject of recurrent information campaigns, does not always lead to their rigorous application during prenatal consultations. It therefore appears that the resistances or the sometimes unsystematic choices of acceptance of the tests and their referents become the object of reflection in the face of the challenge of improving the safe motherhood rate and the attainment of a generation without HIV-AIDS. What are the social attitudes and perceptions related to blood tests and HIV-AIDS testing in pregnant women ? The aim of this study is to understand the social logics underlying the positive or negative attitude of pregnant women to blood tests and the HIV-AIDS test. To address this concern, an essentially qualitative study was carried out among 16 pregnant women and the medical staff of the Urban Sanitary Formation of Ahougnansou in Bouaké (Côte d’Ivoire). The main finding of this study is that attitudes of pregnant women have links to socially situated representations of the disease, stigma, education, income, and perceived risks to social and marital relationships.